PENGARUH LIKUIDITAS, LEVERAGE, DAN SALES GROWTH TERHADAPFINANCIAL DISTRESS - Hesty Erviani Zulaecha; Atik Mulvitasari (Universitas Muhammadiyah Tangerang, 2019)
This study aims to determine the effect of liquidity, leverage, and salesgrowth on partial financial distress on property, real estate and buildingconstruction companies listed on the Indonesia Stock Exchange (IDX).The research period is 3 years in 2015-2017. The population of thisstudy covers all sectors of property, real estate and building constructioncompanies listed on the Indonesia Stock Exchange (BEI) in 2015-2017.The sampling technique uses purposive sampling technique. Based onpredetermined criteria obtained 50 samples of the company. Type ofdata which is secondary data obtained from the site Burssa EfekIndonesia. Data analysis used is regression data panel. The resultsshowed that liquidity had a positive effect on financial distress andnegative leverage on financial distress while sales growth did not affectfinancial distress.